Using selected POCT methods by general practitioners in the Czech Republic - Bělobrádek, Jan; Šídlo, Luděk; Maláková, Kateřina (Casopis lekaru ceskych, 2021)
Point-of-care tests allows for the more effective and rapid diagnosis of acute conditions, better management of chronic disease and the rational use of prescribed medicines. The use of selected non-mandatory tests was analysed in relation to their availability across urban and rural general medical practices in Czechia. Data for 2016 were obtained from the largest health insurance company in Czechia. To categorise the different types of surgery, a spatial model was created applying the OECD regional typology to primary care in Czechia. International normalised ratio (INR) was the most commonly available test, with 53.1 %. In acute care, C-reactive protein (CRP) testing was most extensively present, with 50.9 %. In practice, though, 90 % of these surgeries performed these tests. Both INR and CRP accounted for 42.7 %, whereas 61.3 % used at least one. Contracts of haemoglobin A1c amounted 14.8 %, 38.6 % of practices were not contracted to perform any of three tests, and 43.4 % reported no usage at all. Around half of all general practitioners in Czechia are contracted to provide the most popular non-mandatory point-of-care tests. Reported usage differed among the various surgery typologies, with more peripheral surgeries reporting higher rates.
Keywords: point-of care; Glycated Hemoglobin A; General Practitioners; Chronic Disease; general practice; Humans; Česká republika; praktičtí lékaři; lidé; rural health; glykovaný hemoglobin; chronická nemoc; Glycated Hemoglobin; primary care; Primary care; Czech Republic